Development of learner workbook (LKPD) in collaborative reading instruction at Madrasah Tsanawiyah Renjana Mulia Tuban - Ramadhani, Gita Fitri; Mustofa, Bisri; Al-Anshory, Abdul Muntaqim (Abjadia : International Journal of Education, 2025)
This research develops teaching materials in the form of LKPD (Learner Workbook) based on a collaborative approach to enhance reading skills for seventh-grade students at MTS Renjana Mulia Tuban. The study aims to make learning more effective and meaningful, focusing on the design, validation, effectiveness, and student responses to the LKPD. Utilizing the Research Development (RD) method based on the ADDIE Model, the study involved an experimental class of 19 students and a control class of 18 students. Data collection instruments included questionnaires, interviews, observations, and tests, with analysis performed using statistical methods and Independent Sample T-Test techniques supported by IBM SPSS 21 software. The results indicated that the LKPD consists of 25 pages, receiving validation scores of 86.67% from design experts, 85.00% from material experts, and 96.00% from learning practitioners, all falling within the very feasible category. The average percentage from the student response questionnaire was 85.00%, categorized as very interesting. Hypothesis testing revealed a significant difference in reading skills between the experimental class using LKPD and the control class, with a sig value of 0.001, leading to the rejection of H0 and acceptance of Ha.